Sleep deprivation, oxidative stress and inflammation - Atrooz, Fatin; Salim, Samina (Advances in protein chemistry and structural biology, 2020)
Adequate sleep is essential for normal brain function, especially during early life developmental stages as postnatal brain maturation occurs during the critical period of childhood and adolescence. Therefore, sleep disturbance and/or deficit during this period can have detrimental consequences. Many epidemiological and clinical studies have linked early life sleep disturbance with occurrence of later life behavioral and cognitive impairments. Role of oxidative stress and inflammation has been implicated in sleep deprivation-related impairments. This review article presents a detailed description of the current state of the literature on the subject.